The Influence of Aspects of Interpersonal Skills, Compensation, and Teacher Performance at Madrasah Aliyah Manado - Kili Suci; Roos Marie Stella Tuerah; Shelty Deity Meity Sumual (Researchparks Publishing, 2022)
Many environmental factors can affect teacher performance, three of which are as follows: 1). Principal leadership is the effort of an individual who is trusted as an organizational leader in the school that influences its members including teachers, staff/employees, students, and school committees to realize an educational goal. This research is a survey research that uses a quantitative approach. This quantitative method is a scientific or scientific method because it has fulfilled scientific principles, namely concrete or empirical, objective, measurable, rational, and systematic. In simple terms, there is a positive and significant effect between interpersonal skills and the performance of Madrasah Aliyah teachers in Manado City, where Y = 36.91 + 0.534X1 and the hypothesis value is 0.00 <0.05. Simply put, there is a positive and significant effect between compensation and the performance of Madrasah Aliyah teachers in Manado City, where Y = 39,079 + 0.541X2 and the hypothesis value is 0.00 <0.05. Simultaneously there is a positive and significant effect between interpersonal skills and compensation on the performance of Madrasah Aliyah teachers in Manado City, where the formulaY= 27,583 + 0.361X1+0.412X2 and the hypothesis value is 20.38 > 4,009 or F-count > F-table.